(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article discusses the constructive activities of Alisher Navoi, a vizier, statesman, great thinker, and poet, in the irrigation system of Khorasan. It provides information about the irrigation facilities built under his patronage and initiative.